The Ins and Outs of Colombian Higher Education System (2023)
In this critical reading, the importance of learning about some aspects related to the history, evolution, regulations, achievements, and challenges of higher education in Colombia is raised. This knowledge is especially relevant for tertiary education teachers. With this purpose in mind, the beginnings of such an educational system in the colonial period, as well as the transformations and milestones reached during the various historical, political, and economic changes that our country has had, are described. A description of the current state of tertiary education in Colombia is also offered through statistical data. Additionally, the laws, decrees, and resolutions that make up the legal framework, as well as the governmental bodies in charge of regulating its operation and guaranteeing the quality of the programs, are explained. It also examines the role that icts have in innovation processes and the changes and legislation that have arisen because of the COVID-19 pandemic. It is concluded that, despite its evident evolution, Colombian higher education still faces challenges that require the proposal of pedagogical, technological, and political measures that adjust to the needs of all the agents involved.